The Relationship Between Social Support, Academic Expectation, and Depression on Suicidal Intention Among Youth in Malaysia, India, and Indonesia - Lay Wei Teh; Hui Ting Tung; Qiu Pei Lim; Karisma Indira Salindeho; Iren Puasa Bataly; Nikhil Sudhakar Kokane; Kalahasthi Muni Manikanta Royal; Novita Grisia Rori (AIBPM Publisher, 2024)
This research aims to explore the relationships between social support, academic expectations, and depression regarding suicidal intention among youth in Malaysia, India, and Indonesia. Given the rising concern over youth mental health in these regions, a quantitative approach was employed, utilizing an online questionnaire distributed via Google Forms to gather data from 150 participants. The findings indicate that both academic expectations and depression positively correlate with suicidal intentions, highlighting the significant emotional distress caused by high academic pressures. Conversely, the study revealed that social support negatively correlates with suicidal intention among youth, suggesting that stronger social networks may mitigate these risks. This study contributes to a limited body of research on suicidal ideation in Malaysian, Indian, and Indonesian youth, providing valuable insights into how social support, academic expectations, and depression interplay in influencing suicidal thoughts and behaviors. The results highlight the need for targeted mental health interventions that address the challenges youth face, raising awareness of the harmful effects of academic stress and the value of supportive relationships.